The Implementation of Environmental Cost Accounting in Waste Management in the Bioethanol Industry - Billa, Nurul Salsa; Wahyuni, Hesti; Nurfitriasih, Dyah Metha (Jurnal Ilmiah Akuntansi dan Keuangan, 2025)
This research aims to measure the efficiency of waste management using the concept of Environmental Management Accounting (EMA) based on the Physical Environmental Management Accounting (PEMA) and Monetarily Environmental Management Accounting (MEMA) and analyzed the suitability of environmental cost accounting treatment based on the PSAK No. 201. This research is quantitative descriptive research. Data were collected through interviews and documentation. The data used were production quantities and waste management costs data collected in 2023. The research was conducted at bioethanol industry that processed waste into biogas and liquid organic fertilizer. The research findings revealed in the PEMA calculation there was an imbalance between input and output quantities because the company had not recorded Fusel Oil from the distillation stage. The MEMA calculation revealed the company can save costs incurred to buy gas from PT PGN if it adds two digesters. The highest expenditure in the environmental cost report is in the external failure cost category and presented it simultaneously with other accounts. Therefore, the company should implement environmental cost accounting to control and increase the efficiency of waste management costs.